2018
DOI: 10.2320/matertrans.m2018113
|View full text |Cite
|
Sign up to set email alerts
|

Liberation Characteristics Assessment for Copper Component in PCB Comminution Product by Image Analysis

Abstract: Cu is one of the most valuable metals found in waste printed circuit boards (PCBs). In order to recover the metals from the e-waste, PCB recycling process exploiting physical concentration techniques have widely been applied. Size reduction steps including crushing and grinding are done for liberation of Cu from the non-metallic materials such as glass fiber and epoxy resin. Degree of liberation is an important factor by which liberation performance of comminution process is evaluated. The primary purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, once liberated, it was comminuted rapidly [39]. Park et al [22] suggested that the comminution of objects consisting of two substances with mutually different ductilities shows the following behavior with a decrease in particle size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, once liberated, it was comminuted rapidly [39]. Park et al [22] suggested that the comminution of objects consisting of two substances with mutually different ductilities shows the following behavior with a decrease in particle size.…”
Section: Discussionmentioning
confidence: 99%
“…PCB must be pulverized into particles to effectively liberate and separate Cu [18,21,22]. According to a previous study, it should be comminuted to approximately 150 µm or less (e.g., liberation size) [6,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The printed circuit boards (PCBs) present in almost every single piece of electronic equipment, and account for roughly 5 wt% of the entire e-waste currently produced. Nevertheless, they carry the most important share of the valuable and also toxic metals [2,3]. This creates an urgent need for recovering/recycling valuable materials from PCBs.…”
Section: Introductionmentioning
confidence: 99%